Project Management : A comprehensive description of Theory and Practice - Madauss, Bernd-J (Springer, 2024)
This book comprehensively addresses all essential aspects of modern project management in theory and practice. For authorities and companies engaged in executing national and international project tasks, the application of professional project management is a crucial requirement to successfully compete in the global market. The book provides detailed descriptions of project management processes accompanied by practical examples